2016
DOI: 10.1111/anu.12410
|View full text |Cite
|
Sign up to set email alerts
|

Poly-beta-hydroxybutyrate-enrichedArtemiasp. for giant tiger prawnPenaeus monodonlarviculture

Abstract: The beneficial effects of PHB as supplement for giant tiger prawn Penaeus monodon postlarvae using a short‐term enrichment strategy via Artemia were examined. The effects of co‐supplementing with a lipid emulsion were also evaluated to determine whether it yielded an additional benefit. Results on the average weight and larval development were not significantly different among postlarvae fed the different dietary treatments, indicating that PHB supplementation could not be used to stimulate growth in P. monodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…The observed change in the intestinal microbial community is hypothesized to develop due to the degradation of PHB into SCFAs, causing a decrease in the GI pH, which inhibits the growth of certain pathogenic bacteria (De Schryver et al., , ; Defoirdt et al., ). Accordingly, it could be demonstrated that PHB effectively enhances the disease resistance in aquatic invertebrates (Ludevese‐Pascual et al., ; Sui et al., ) and fish. Dietary PHB protected gnotobiotic Nile tilapia larvae (Situmorang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The observed change in the intestinal microbial community is hypothesized to develop due to the degradation of PHB into SCFAs, causing a decrease in the GI pH, which inhibits the growth of certain pathogenic bacteria (De Schryver et al., , ; Defoirdt et al., ). Accordingly, it could be demonstrated that PHB effectively enhances the disease resistance in aquatic invertebrates (Ludevese‐Pascual et al., ; Sui et al., ) and fish. Dietary PHB protected gnotobiotic Nile tilapia larvae (Situmorang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The overall status of the postlarvae at the start of the experimental trial and the survival and growth parameters at the end of the trial were examined according to the methods described by Ludevese‐Pascual et al, (). The number of surviving postlarvae in each tank was counted and percentage survival was computed following the formula of Thompson and Bergersen ():Survival%=XN×100where X is the number of larvae present at the end of the experimental period and N is the number of larvae at stocking (day 0).…”
Section: Methodsmentioning
confidence: 99%
“…The mean weight within each replicate tank was determined by collecting all surviving postlarvae that were not used in the stress test and challenge trial. These were sacrificed by immersion in ice cold seawater and subsequently processed according to the methods described by Ludevese‐Pascual et al, (). The mean daily growth (ADG) was calculated within each replicate tank as mentioned in weight measurement and the mean ADG for each treatment was calculated following the formula of Ravuru and Mude ():…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations